Candunga: fissuras do presente ressignificando uma certa Amazônia e um certo nordeste no romance de Bruno de Menezes - WANZELER, Rodrigo de Souza (Universidade Federal do Pará, 2015)
Since the 60’s of the last century, the studies about culture become more explored like tool of observation in many areas. The culture, in this sense, is so complexified by it be a result of a contact between different social groups and, so, to necessity of a deep study about its formation. The literature, in this context, reflects this cultural complexity. In this aspect, the literature, used like history and culture forms, is a great reference of information that can expose many mysteries about the cultural formation in different levels, from local to global. The conjuncture of a biggest intercultural contact reaches the Amazon area, being reflected, mainly, by the migratory aspect after the top of commercialization of rubber, the called boom of rubber, during the second part of 19th century and the first part of 20th century. The Bruno de Menezes’ literature, in Candunga, makes references to this reality linked to humans displacements, more directly gives focus to Railroad Belém-Bragança. In this sense, our focus of study will be the relation established between migrants northeastern and the Amazon caboclos, this last represented by the voice of Candunga’s narrator, detainer of a cultural discourse favorable to Amazon man of bragantina zone. We’ll perceive that occurs a cultural and identity conflict in many parts of Candunga by the emergency of differences between caboclos and northeastern. We’ll note an affirmation discourse, by the narrator, of Amazon culture in detriment of northeastern culture. But, we’ll don’t forget to emphasize the cultural hybridization present in the Bruno de Menezes’s novel.